Assessment of knowledge, perception, and awareness about self-medication practices among university students in Nepal. Issue 1 (January 2021) - Shah, Krishnandan; Halder, Shimul; Haider, Syed Shabbir
Abstract: The objective of the present study was to assess the perceptions, knowledge, and awareness of self-medication practice among the university students in Nepal. This descriptive cross-sectional, questionnaire-based study was conducted on randomly selected 620 students from three different universities in Nepal. The study results revealed that 95.4% of students had reported self-medication, among which analgesics and antipyretic medications were mostly used (66 %); followed by anti-ulcerants (35.3%), antibiotics (33.9%), anti-allergic preparations (20%), and other categories (10.3%) of drugs. Study results also showed that, the major cause of self-medication was minor illness, and the prescriptions which were previously used to treat the similar disease conditions were the main source of motivation to do so. A significant portion of the respondents believed that self-medication might be acceptable to treat minor illness. Furthermore, students demonstrated variable responses regarding the doses, safety, toxicities, and health hazards towards self-medication without having appropriate knowledge of drugs. The findings of this study revealed the necessity of building awareness and strict implementation of the jurisdiction to minimize the practice of self-medication. Abstract : Self-medication; University students; Awareness; Perception; Nepal.